Modern status of the problem of hallux valgus surgery HALLUX VALGUS (Review) - Liabakh , A.P.; Rudenko , R.I. (TERRA ORTHOPAEDICA, 2020)
Summary. The problem of hallux valgus (HV) surgery remains actual. There are some unresolved social and medical issues in particular: great widening of HV, patient’s unsatisfaction of cosmetic and functional results, imperfection of classifications, discrepancy between surgeon’s and patient’s expectation from surgery. The possibility of Manchester Grading Scale using can correctly bypass the methodological imperfection of classifications grounded on scialogical parameters. The conclusion was done about the necessity of comparative studies concerning to the effectiveness of surgical methods.